Measurement of the Psychosocial Work Environment in Spanish: Validation of the Psychosocial Factors Questionnaire 75 (PSF-Q75) to Capture Demands and Resources at Different Levels of Analysis - Madrid, Hector P.; Vasquez, Cristian A.; Patterson, Malcolm (Frontiers in Psychology, 2020)
The psychological work environment is composed of both stressful and motivational work conditions at different levels of analysis. However, most relevant theory and research lack an integrative conceptualization and appropriate instrumentation to account for this work context structure. These limitations are particularly present in non-mainstream populations, such as the Spanish community of researchers and practitioners. In this study, based on the job demands-resources model, we present an updated conceptualization in which stressful and motivational psychosocial factors are integrated and defined at the job, the group, and the organizational level of analysis into a single conceptualization. Furthermore, derived from this conceptualization, we present a study of the development and validation of a questionnaire to account for the psychosocial work environment in Spanish, labeled Psychosocial Factors Questionnaire 75 (PSF-Q75), which provides measures for 23 different psychosocial factors. The results of this study supported the questionnaire’s construct, convergent, divergent, and predictive validity, together with its reliability. Thus, this conceptualization and questionnaire provides researchers and partitioners with a more comprehensive approach to the assessment of the psychosocial work environment and promises benefits for interventions in the workplace.